Interindividual variability in dabigatran and rivaroxaban exposure: contribution of ABCB1 genetic polymorphisms and interaction with clarithromycin. (6th February 2017) - Gouin‐Thibault, I.; Delavenne, X.; Blanchard, A.; Siguret, V.; Salem, J. E.; Narjoz, C.; Gaussem, P.; Beaune, P.; Funck‐Brentano, C.; Azizi, M.; Mismetti, P.; Loriot, M. A.
Abstract : Essentials Rivaroxaban and dabigatran are substrates of the P‐glycoprotein (P‐gp) encoded by the ABCB1 gene. We tested the effect of ABCB1 polymorphisms and of a P‐gp inhibitor on both drugs' pharmacokinetics. The ABCB1 genotype was not a clinically relevant determinant of both drugs' pharmacokinetics. Administration of P‐gp inhibitors with dabigatran or rivaroxaban should be exercised with caution. Summary: Background: The direct oral anticoagulants (DOACs) dabigatran and rivaroxaban are both substrates of the P‐glycoprotein (P‐gp) transporter, encoded by the ABCB1 gene. Rivaroxaban is metabolized by cytochrome P450 A4 (CYP3A4). Interindividual variability in DOAC exposure and frequent P‐gp‐associated drug–drug interactions have been described in patients. Objective: To assess the influence of ABCB1 polymorphisms on the pharmacokinetics of dabigatran and rivaroxaban, associated or not with clarithromycin, a P‐gp and CYP3A4 inhibitor. Methods: Sixty healthy male volunteers, selected according to ABCB1 genotype (20 homozygous mutated, 20 heterozygous mutated, and 20 wild‐type for haplotype 2677‐3435), were included in this randomized, two‐center, crossover study. All received sequentially a single dose of dabigatran etexilate (300 mg) and rivaroxaban (40 mg) associated or not with clarithromycin. Peak plasma concentration and area under the curve (AUC) were compared across the three ABCB1 genotypes. The effect of clarithromycin on dabigatran or rivaroxaban pharmacokinetics was assessed. Results: Interindividual coefficients of variation for AUC were 77% for dabigatran and 51% for rivaroxaban. ABCB1 genotype did not significantly affect drug pharmacokinetics: AUC ratios between mutant‐allele carriers and wild‐type volunteers were 1.27 (95% confidence interval [CI] 0.84–1.92) and 1.20 (95% CI 0.96–1.51) for dabigatran and rivaroxaban, respectively. Clarithromycin coadministration led to a two‐fold increase in both drugs' AUC, irrespective of ABCB1 genotype: ratios of geometric means were 2.0 (95% CI 1.15–3.60) and 1.94 (95% CI 1.42–2.63) for dabigatran and rivaroxaban, respectively. Conclusions: ABCB1 genotype is not a significant determinant of interindividual variability in dabigatran and rivaroxaban pharmacokinetics. The levels of one drug did not predict the levels of the other. Coadministration of a P‐gp/CYP3A4 inhibitor with dabigatran or rivaroxaban may warrant caution in patients at risk of overexposure.